Legal Review Act on Cryptocurrency (Bitcoin) As an Inflation Control in Indonesia - Rahmat Mustaqim Adi Nugroho; Nanang Sudarsono; Achyar Rosandi; Akbar, Zaki (Faculty of Law, Universitas Pekalongan, 2024)
The goals of these brief are to identifies and analyze how the role of Act in backups Rupiah strength against the exchange of decentralize finance block-chain based cryptocurrency (known as Bitcoin or BTC) whereas does not requires swift-code alike printed or FIAT as a early detection of state to print collateral or guarantee on foreign exchange rate. Within act or preparation of ratification upcoming act, remembered by the 13th August 2025 Rupiah exchange has weakened since last 5 year along +/- 3.000 Rupiah per- USD numbered 16.164 Rupiah against 1 USD became the basis of Act to be frontier guardian to prevent valuation of inflation and empowered Rupiah in global market exchange. Otherwise thus valuation were countered back by BTC on every-world currencies since 2016 itself has gained the upscale as much as 32.018,52% the number that should concerned and potentially capable to brought a nation into failure if it is not restricted immediately by the Gration or Acts that defend a currency rate in every state.